Devolpment and evaluation of scripts during medical training - Arceo, María Dolores (Revista del Hospital Italiano de Buenos Aires, 2013)
Research indicates that knowledge drives student learning. The assessment of clinical competence, including clinical reasoning, which is the guide of all medical action, represents a big challenge in medical education. Therefore, valid and reliable assessment of clinical reasoning during clinical development should be considered essential. The script concordance test (SCT) was designed to accomplish this objective. In this article we will analyse the process of development of clinical reasoning and the SCT utility for measuring it. We will also elaborate a guide for the construction of the SCT
Keywords: scripts concordance test; assessment; medical education